Global disparities in cancer supportive care: An international survey - Alexandre Chan; Lawson Eng; Changchuan Jiang; Mary Dagsi; Yu Ke; Mary Tanay; Cristiane Bergerot; Niharika Dixit; Ana Cardeña Gutiérrez; Ana I. Velazquez; Farhad Islami; Enrique Soto‐Perez‐de‐Celis (Cancer Medicine)
Abstract Background The global cancer burden is rising, particularly in low‐ and middle‐income countries (LMIC), highlighting a critical research gap in understanding disparities in supportive care access. To address this, the Multinational Association of Supportive Care in Cancer (MASCC) Health Disparities Committee initiated a global survey to investigate and delineate these disparities. This study aims to explore and compare supportive care access disparities between LMIC and High‐Income Countries (HIC). Methods An online cross‐sectional survey was conducted among active members of MASCC. Members, representing diverse healthcare professions received email invitations. The survey, available for 3 weeks, comprised sections covering (1) sociodemographic information; (2) clinical service/practice‐related disparities in their region/nation; (3) population groups facing disparities within their region or country. Chi‐squared or Fisher's exact test for cross‐sectional analyses, and a multivariable logistic regression model was employed for statistical analysis. Results A total of 218 active members participated, with one‐quarter (26.6%) from LMIC and 18.4% ethnic minorities, timely cancer care (43.7%) and timely supportive care (45.0%) emerged as the most pressing disparities globally. Notably, participants from LMIC underscored cancer drug affordability (56.4%) and supportive care guideline implementation (56.4%) as critical issues. Economically disadvantaged populations were noted as more likely to face disparities by both LMIC and HIC (non‐US‐based) respondents, while US‐based respondents identified racial/ethnic minorities as facing more disparities. Conclusion This global survey reveals significant disparities in cancer supportive care between LMIC and HIC, with a particular emphasis on medication affordability and guideline implementation in LMIC. Addressing these disparities requires targeted intervention, considering specific regional priorities.